Left Atrial Mechanics and Functional Capacity in HFpEF pts with Paroxysmal Atrial Fibrillation - Moya, Ana; Kodeboina, Monika; Katbeh, Asim; Penicka, Martin; Verstreken, Sofie; Vanderheyden, Marc (Cardiology and Cardiovascular Medicine, 2023)
Introduction: Patients (pts) with paroxysmal atrial fibrillation are at risk for developing heart failure with preserved ejection fraction(HFpEF) and often have an impaired exercise capacity. Since left atrial (LA) pressure plays a major role in the exercise intolerance, we aimed to characterize the contribution of resting LA mechanical properties, assessed by two-dimensional speckle tracking echocardiography upon exercise capacity. Purpose: To evaluate relationship between LA mechanics, measured by LA strain (LAS) and parameters of exercise capacity in pts with paroxysmal atrial fibrillation. Methods: The study included 54 pts (64 ± 10years, 76 % males) with dyspnea (NYHA≥II), paroxysmal atrial fibrillation and preserved LV ejection fraction (≥50%). The likelihood of HFpEF was estimated using H2FPEF score. During sinus rhythm, all patients underwent speckle tracking echocardiography and cardiopulmonary exercise testing (CPET). Peak oxygen uptake (VO2peak) served as measure of functional capacity and ventilation/carbon dioxide output slope(VE/VCO2) as surrogate of ventilation/perfusion mismatch. Results: LA contractile strain(S) and strain rate(SR) showed significant correlation with VO2peak(both p < 0.05). LA reservoir, conduit and contractile LAS, all had significant relationship with VE/VCO2 slope (all p<0.050). Pts with LASR above the median had significantly higher VE/VCO2 (p=0.025) and lower VO2peak(p=0.010). In contrast, no correlations were observed between exercise parameters and LA volumes or any other echocardiographic indices. Conclusions: In HFpEF VO2peak and VE/VCO2 are closely related to LA contractile strain, suggesting that abnormalities in LA mechanics may contribute to t